Public university educators’ understanding and conception of soft skills for educators - Md Ali, Ruzlan; Shaffie, Fuziah; Mohd Yusof, Fahainis (2016)
There is still no formally agreed upon, universal set of soft skills.The lack of soft skills competence among graduates from public universities (PUs) is an issue and a reason for unsuccessful job applications.Students in PUs need to be guided to acquire the relevant soft skills and need to have role models to be professionally and socially competent. They can actually learn much from their lecturers or educators as role models.In a recent exploratory study, educators selected from PUs were individually interviewed to capture their understanding and conception of soft skills as part of their professional contribution to support the effort to foster and ensure the acquisition of soft skills among university students in Malaysia.This paper provides a glimpse into three PU educators’ understanding and conception of soft skills within their current professional.Their thoughts on soft skills and their propositions of other possible skills that could be included as soft skills, and soft skills that PU educators ought to possess, could provide early ideas and initiatives towards the construction of a “soft skills framework” for PU educators, which could serve as guideline for educators to develop, facilitate, and enhance soft skills among graduate students.